Analisis Penerjemahan Metafora: Studi Kasus Metafora Dalam Novel Yukiguni Karya Kawabata Yasunari Dan Terjemahannya Daerah Salju Oleh Ajip Rosidi - Rini Widiarti (Bina Nusantara University, 2011)
This study aims to describe the form of metaphorical translation of the source language (SL), Japanese, into the target language (TL), Indonesian, as well as the equivalences in TL. The study also explains any the translation procedures used by the translator to get a natural translation so that the metaphor contained in the target text is able to give the same impression with the original text. Data were collected from the work of Kawabata Yasunari “Yukiguni” Novel and the translation